2009
DOI: 10.1016/j.jml.2009.06.004
|View full text |Cite
|
Sign up to set email alerts
|

A beautiful day in the neighborhood: An event-related potential study of lexical relationships and prediction in context

Abstract: Two related questions critical to understanding the predictive processes that come online during sentence comprehension are 1) what information is included in the representation created through prediction and 2) at what functional stage does top-down, predicted information begin to affect bottom-up word processing? We investigated these questions by recording event-related potentials (ERPs) as participants read sentences that ended with expected words or with unexpected items (words, pseudowords, or illegal st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
193
7

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(229 citation statements)
references
References 66 publications
26
193
7
Order By: Relevance
“…Instead, they provide empirical support for Laszlo and Federmeier's (2009) proposal that "quantitative shifts in the timing of processing can potentially lead to qualitative differences in what particular facets of semantics come to be linked up with a given input" (p.32) and highlight the importance of timing considerations in the study of prediction (cf. Dambacher et al, 2012;Wlotko & Federmeier, 2015).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Instead, they provide empirical support for Laszlo and Federmeier's (2009) proposal that "quantitative shifts in the timing of processing can potentially lead to qualitative differences in what particular facets of semantics come to be linked up with a given input" (p.32) and highlight the importance of timing considerations in the study of prediction (cf. Dambacher et al, 2012;Wlotko & Federmeier, 2015).…”
Section: Discussionmentioning
confidence: 81%
“…For example, listeners are more likely to direct their eye-gaze to a picture of an edible object (e.g., a cake) when they hear the beginning of an utterance like 'The boy will eat…' compared to a neutral utterance such as 'The boy will move…' (Altmann & Kamide, 1999). Further, much evidence has suggested that comprehenders compute rich expectations about upcoming inputs at multiple levels of representation (syntactic: Ilkin & Sturt, 2011;Lau, Stroud, Plesch, & Phillips, 2006;Levy, Fedorenko, Breen, & Gibson, 2012;Omaki et al, 2015;Staub & Clifton, 2006;Wicha et al, 2004;Van Berkum et al, 2005;Yoshida, Dickey, & Sturt, 2013;lexico-semantic: Federmeier & Kutas, 1999;Kutas & Hillyard, 1984;Otten & Van Berkum, 2008;Szewczyk & Schriefers, 2013; phonological and orthographic: Delong et al, 2005;Dikker, Rabagliati, Farmer, & Pylkkanen, 2010;Dikker, Rabagliati, & Pylkkänen, 2009;Farmer, Yan, Bicknell, & Tanenhaus, 2015;Kim & Lai, 2012;Laszlo & Federmeier, 2009). Here, we operationally define 'prediction' as the pre-activation of stored representations before the bottom-up input is encountered, and we will make no a priori assumptions regarding the nature of the mechanisms involved (e.g., whether they are automatic or controlled).…”
Section: Prediction In Language Comprehensionmentioning
confidence: 99%
“…Unification is expected to be always harder for semantic incongruities, which should lead to stronger responses in the BOLD signal 3 There are at least two ways to account for this fact (Laszlo & Federmeier, 2009): one based on attractor networks (Hopfield, 1982), the other on Bayesian predictive coding (Friston, 2005). The theory presented in Sections 4 and 5 is more consistent with the former framework, which is also a more standard approach to language in the brain than Bayes.…”
Section: Unification and Integrationmentioning
confidence: 99%
“…Other studies that reported modulations of the N400 component suggest that pre-activation can be remarkably specific. Contextual-semantic cues can selectively activate semantic (Federmeier & Kutas, 1999;Kutas & Hillyard, 1980, 1984, morphological (Otten, Nieuwland, & Van Berkum, 2007;Wicha, Moreno, & Kutas, 2004), phonological (De Long et al, 2005), and orthographic (Laszlo & Federmeier, 2009) information about an expected sentence completion. Preliminary evidence indicates that the N400 can also be modulated by expectations of word category: Hinojosa, Moreno, Casado, Mũ noz, and Pozo (2004) found that correct but syntactically unexpected words evoke a larger N400 than syntactically expected words.…”
mentioning
confidence: 99%
“…This conclusion is further corroborated by evidence that illegal letter strings, like a row of Xs, do not modulate the N400 and yield no repetition effect when task-irrelevant (cf. Laszlo & Federmeier, 2009;Laszlo, Stites, & Federmeier, 2012).…”
Section: Comparisons With Earlier Findingsmentioning
confidence: 99%